Aesthetics, simulacra, and lifestyle consumption: A social practice in the representational space of “Ada Apa Dengan Kopi” café on Gen-Z - Shabihah Agustiarmaputri (Jurnal Sosiologi Dialektika, 2025)
This study examines the symbolic and aesthetic construction of the coffee shop Ada Apa Dengan Kopi as a simulacrum—a representation that mediates and dominates social reality—and its implications for consumption practices and identity formation among Generation Z. Employing a qualitative phenomenological approach, the research seeks to understand the subjective meanings that Gen Z visitors construct through activities such as socializing, studying, working from the café (WFC), and taking personal “metime” within the café space. Drawing on Jean Baudrillard’s theories of simulacra, simulation, and hyperreality, the analysis highlights how aesthetic elements (interior design, product presentation, atmosphere) function as signs that not only reflect reality but also shape and precede the café’s social reality. The findings reveal that Ada Apa Dengan Kopi provides a representational space in which Gen Z individuals perform their social and aesthetic identities, experience existential fulfillment and prestige amid the fragility of everyday reality. This space constructs a hyperreal condition where coffee becomes not only a commodity but also a symbol of status and identity and a stage for lifestyle performance. Thus, this coffee shop becomes a simulacrum, namely, the social reality of Gen Z is constructed through signs and aesthetics that paradoxically produce consumption and social interaction in the context of contemporary urban culture.